1997
DOI: 10.1002/chem.19970030715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melamine‐Amphiphile Structure on the Extent of Two‐Dimensional Hydrogen‐Bonded Networks Incorporating Barbituric Acid

Abstract: Four alkyl melamine amphiphiles cach containing identical triads of hydrogen-bonding sites (hydrogen donor, acceptor, and donor) but different numbers of alkyl chains were examined in order to determine their monolayer properties and binding behavior towards barbituric acid (BA). Their structural organization in supramolecular assemblies at the air-water interface was affected by the bulkiness of the hydrophobic part of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 27 publications
4
65
0
Order By: Relevance
“…In a typical extended hydrogen bonding array, alternate hydrogen pairs between melamine and barbituric acid or related molecules have been investigated both in solution [164,165] and at the air-water interface [166][167][168]. An AFM image of didodecylmelamine molecules bound to a barbituric template was readily observed (Fig.…”
Section: Structure Formation At Dynamic Surfacementioning
confidence: 95%
“…In a typical extended hydrogen bonding array, alternate hydrogen pairs between melamine and barbituric acid or related molecules have been investigated both in solution [164,165] and at the air-water interface [166][167][168]. An AFM image of didodecylmelamine molecules bound to a barbituric template was readily observed (Fig.…”
Section: Structure Formation At Dynamic Surfacementioning
confidence: 95%
“…2A) [22 •• ]. Although barbituric acid derivatives have been widely investigated from the point-of-view of their complementary hydrogen bonding with melamine at the air-water interface [23][24][25], the hydrogen bonding between barbituric acid derivatives within monolayers was utilized in this case. When the film was compressed to the inflection point in the π-A isotherm, spiral nanofibers were observed by atomic force microscopic (AFM) observation.…”
Section: Chiral Recognition Within Monolayer Componentsmentioning
confidence: 99%
“…The linkage, melamine ring, used to connect two monomeric PDIs units, is well known for its hydrogen bonding with barbituric acid and forming face-to-face conformation for the connected two chromophores [43][44][45][46] and therefore provides possibility for ordering the molecules in solid film through hydrogen bonding [33,34,47,48]. The detailed synthetic procedures together with the structure characterization are described in supplementary material.…”
Section: Molecular Design and Synthesismentioning
confidence: 99%
“…This supramolecular system was also studied at the air-water interface. In contrast to the traditional belief that hydrogen bonding is not so efficient in aqueous solution, studies by a few research groups demonstrated that a highly ordered and rigid linear network was formed between amphiphilic barbituric acid and melamine with its complementary components in Langmuir and Langmuir-Blodgett films [31][32][33][34]. Moreover, it was reported by Huo et al that such a linear hydrogen bonding network could have a dramatic effect on the photopolymerization of a diacetylene monolayer film and the properties of the resulting polydiacetylene film [35,36].…”
Section: Introductionmentioning
confidence: 98%